2008
DOI: 10.1039/b716353c
|View full text |Cite
|
Sign up to set email alerts
|

Calcium phosphate mineralization beneath monolayers of poly(n-butylacrylate)–block–poly(acrylic acid) block copolymers

Abstract: Amphiphilic poly(acrylic acid)-block-poly(n-butylacrylate) block copolymer films at the air-water interface have been mineralized with calcium phosphate. The polymers form stable monolayers at the free surface. Their stability is virtually independent of ion strength or pH changes in the subphase. The outcome of calcium phosphate crystallization depends on the calcium and phosphate concentrations, the stirring rate of the subphase, and the subphase pH. At low calcium and phosphate concentrations (2 mM), unifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
51
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 61 publications
(73 reference statements)
11
51
2
Order By: Relevance
“…[43][44][45] To a large extent, this is due the well-known biopassivation abilities of PEO 46 and the strong interaction of poly(electrolyte)s with inorganic ions [47][48][49][50] and surfaces. 47,48,[51][52][53] The combination of highly charged remineralizition-enhancing 48,49,[54][55][56][57][58][59][60][61][62] or dissolution-limiting 63,64 polymer segments with the biopassivation of PEO is thus a viable strategy towards multifunctional polymers providing both anti-biolm and remineralization-enhancing behavior in one single system.…”
Section: 26mentioning
confidence: 99%
“…[43][44][45] To a large extent, this is due the well-known biopassivation abilities of PEO 46 and the strong interaction of poly(electrolyte)s with inorganic ions [47][48][49][50] and surfaces. 47,48,[51][52][53] The combination of highly charged remineralizition-enhancing 48,49,[54][55][56][57][58][59][60][61][62] or dissolution-limiting 63,64 polymer segments with the biopassivation of PEO is thus a viable strategy towards multifunctional polymers providing both anti-biolm and remineralization-enhancing behavior in one single system.…”
Section: 26mentioning
confidence: 99%
“…8b . It is remarkable that an interesting phenomenon in the recent publication, Casse et al (Casse, et al, 2008) has found that even a rather flexible matrix like the block copolymers film at the vapor-liquid interface not only leads to uniform particles with identical particle sizes, but also can act as a tool for the 2D arrangement of the resulting particles in a nearcrystalline order in a distorted hexagonal lattice. Regulating mineralization on the atomic (crystal phase) and the nanoscopic (particle size and shape) scale in the reported work is often encountered in the case that inorganic crystals are mineralized under organic matrix templates.…”
Section: Reproduced By Permission Of the Royal Society Of Chemistry)mentioning
confidence: 99%
“…Moreover, the block copolymer film at the air/water interface also acts as a tool for the 2D arrangement of the resulting particles in a nearcrystalline order [46]. The Wentrup-Byrne group has demonstrated that the amount of phosphate groups in the matrix polymers [poly(monoacryloxyethyl phosphate) and poly(2-(methacryloyloxy)-ethyl phosphate)] had great impact on the calcium phosphate crystallization.…”
Section: Introductionmentioning
confidence: 99%